Effectiveness of Radiotherapy in Heterotopic Ossification - Yasemin Benderli Cihan; Alaettin Arslan (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2015)
Objective: Heterotopic ossification (HO) is a biological process characterized by de novo bone formation in tissues which should not undergo ossification in normal condition. Frequently, it is a complication that occurs after head injuries, spinal cord injuries, cerebrovascular events, burns,fractures, dislocations and joint replacements. Etiopathogenesis is unclear in HO. Clinical symptoms and signs become apparent at late phase. Limitation and pain occur by advancing disease. The diagnosis and management are of importance. Non-steroidal anti-inflammatory drugs (NSAIDs) and radiotherapy (RT) are preferred in prophylaxis. The aim of present study was to assess safety and effectiveness of radiation therapy in preventing HO. Material and method: Data of patients received RT with a diagnosis of HO between 2005 and 2013 were retrospectively reviewed. Findings: Overall 12 patients aged 20-72 years, including 8 men and 4 women, received RT for HO prophylaxis. HO incidence was highest in hip joint (n=7); followed by elbow (n=3) and knee joints (n=2). Of these patients, 7 received postoperative RT while 5 received RT for HO prophylaxis.RT was given in a single fraction at a dose of 7 Gy (6-8 Gy). Patients received postoperative RT was also given indomethacin (75 mg/day) over 15-20 days. No RT-related complication was observed in any of the patients. Imaging modalities were used in follow-up. In addition, Broker's Grading Scale was used for the assessment of lower extremities whereas Hastings and Graham Grading Scale was used for upper extremities. Median follow-up was 25.3 months (range: 2-69 months). No radiological HO recurrence was observed in any of the patients received postoperative RT. Conclusion: RT in combination with NSAIDs is a safe and effective therapeutic modality in the prophylaxis of patients at high-risk for HO development.